2008
DOI: 10.1073/pnas.0711928105
|View full text |Cite
|
Sign up to set email alerts
|

Absence of equilibrium cluster phase in concentrated lysozyme solutions

Abstract: In colloidal systems, the interplay between the short range attraction and long-range repulsion can lead to a low density associated state consisting of clusters of individual particles. Recently, such an equilibrium cluster phase was also reported for concentrated solutions of lysozyme at low ionic strength and close to the physiological pH. Stradner et al. [(2004) Equilibrium cluster formation in concentrated protein solutions and colloids. Nature 432:492-495] found that the position of the low-angle interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
201
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(220 citation statements)
references
References 35 publications
14
201
2
Order By: Relevance
“…In contrast to our previous findings (1), Shukla et al (2) claim the absence of clusters in concentrated lysozyme solutions. This claim is based on scattering data that show no significant differences from our data, where conditions are similar.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our previous findings (1), Shukla et al (2) claim the absence of clusters in concentrated lysozyme solutions. This claim is based on scattering data that show no significant differences from our data, where conditions are similar.…”
contrasting
confidence: 99%
“…Furthermore, fits of form and structure factors result in values for the pair potential but cannot provide direct information on the presence of monomers and/or clusters. Nonetheless, for a potential with similar values as determined by Shukla et al (2), MD simulations have confirmed the presence of clusters (3). Therefore, their data (2) actually confirm our earlier data and interpretation (1) that the peak position is concentration-independent and clusters are present in lysozyme solutions, which, as stated in both of our titles, are concentrated.…”
supporting
confidence: 89%
“…This can only be done by means of well-converged CpH simulations. Such an observation for LYZ might indicate a promising way to shed light on the understanding of the apparent paradox involved in the LYZ self-association (Shukla et al 2008). …”
Section: Simplified Models Applications In Biomolecular Systemsmentioning
confidence: 94%
“…Such peculiar interactions are ubiquitous in soft materials: as few examples, they were used to model protein solutions [1][2][3][4][5], colloids [1,6,7], star polymers [8]. The long-range repulsion is generally attributed to the weakly screened charge carried by the colloidal molecules, or to the presence of cosolutes in the solution [9], whereas the short-range attraction arises from several different mechanisms, including van der Waals interactions, depletion forces, hydrophobic effects [10][11][12].…”
Section: Introductionmentioning
confidence: 99%